Russian foreign policy [ sources and implications - Oliker, Olga (RAND Corporation monograph series, 2009)
As Russia's economy has grown, so have the country's global involvement and influence, which often take forms that the United States neither expects nor likes, as the August 2008 conflict in Georgia demonstrated. Despite the two countries' many disagreements and the rising tension between them, the United States and Russia share some key interests and goals. In this monograph, the authors assess Russia's strategic interests and the factors that influence Russian foreign policy broadly. They examine Russia's domestic policies, economic development, and views of the world, as well as how these translate into security policies at home and abroad. They then consider the implications of Russia's evolving approaches for U.S. interests. The authors find that Russia's rising confidence will continue to create challenges for U.S. policymakers. The U.S. goal must therefore be to improve relations with Russia and build on shared views and shared interests, rather than to pursue coercive mechanisms that can easily backfire. Among other steps, the authors recommend that Washington vigorously pursue new arms control agreements with Moscow allay Russian fears about proposed U.S. missile defenses in Europe reevaluate its promotion of energy pipeline routes that circumvent Russia resume consistent, high-level consultations, including military-to-military contacts. If Russo-U.S. relations do not improve, the United States must find ways to keep poor relations with Russia from turning into adversarial ones. The Department of Defense and U.S. Air Force have important roles to play in either scenario